SKP2- and OTUD1-regulated non-proteolytic ubiquitination of YAP promotes YAP nuclear localization and activity - Yao, Fan; Zhou, Zhicheng; Kim, Jongchan; Hang, Qinglei; Xiao, Zhenna; Ton, Baochau N.; Chang, Liang; Liu, Na; Zeng, Liyong; Wang, Wenqi; Wang, Yumeng; Zhang, Peijing; et al. (Nature communications, 2018)
Dysregulation of YAP localization and activity is associated with pathological conditions such as cancer. Although activation of the Hippo phosphorylation cascade is known to cause cytoplasmic retention and inactivation of YAP, emerging evidence suggests that YAP can be regulated in a Hippo-independent manner. Here, we report that YAP is subject to non-proteolytic, K63-linked polyubiquitination by the SCF SKP2 E3 ligase complex (SKP2), which is reversed by the deubiquitinase OTUD1. The non-proteolytic ubiquitination of YAP enhances its interaction with its nuclear binding partner TEAD, thereby inducing YAP’s nuclear localization, transcriptional activity, and growth-promoting function. Independently of Hippo signaling, mutation of YAP’s K63-linkage specific ubiquitination sites K321 and K497, depletion of SKP2, or overexpression of OTUD1 retains YAP in the cytoplasm and inhibits its activity. Conversely, overexpression of SKP2 or loss of OTUD1 leads to nuclear localization and activation of YAP. Altogether, our study sheds light on the ubiquitination-mediated, Hippo-independent regulation of YAP. Regulation of Yes-associated protein (YAP) through the Hippo pathway is well established, but its Hippo-independent regulation remains to be elucidated. Here, the authors show that non-proteolytic ubiquitination presents another means of YAP regulation, promoting its nuclear localization and activity.